Proses pembentukan identitas diri remaja - Purwadi Purwadi (Universitas Ahmad Dahlan, 2004)
Adolescent is on the spesific psychological development phase. They face confusion in self identity finding. This phase is so crucial for the next process of adolescence psychological development. This paper try to reveal theoritically the process of self identity formation. It can be explained from the process of self identity establishment of the adolescent that is influence by antecedent followed the pattern of m-a-m-a cyle, depends on the quality of exploration process and comitment and the identity status.